It Takes Merchandising To Tell the Science Story - Robert E. Enlow (Journal of Applied Communications, 1979)
The British Broadcasting Corporation called a USDA research leader in Peoria - yes, Peoria - Illinois, in September for information about plants that yield botanochemicals. (Papers from the National Agricultural Science Information Conference, Ames, Iowa.)